Polymer‐Induced Surface Modifications of Pd‐based Thin Films Leading to Improved Kinetics in Hydrogen Sensing and Energy Storage Applications1. (22nd September 2014) - Ngene, Peter; Westerwaal, Ruud J.; Sachdeva, Sumit; Haije, Wim; de Smet, Louis C. P. M.; Dam, Bernard
Abstract The catalytic properties of Pd alloy thin films are enhanced by a thin sputtered PTFE coating, resulting in profound improvements in hydrogen adsorption and desorption in Pd‐based and Pd‐catalyzed hydrogen sensors and hydrogen storage materials. The remarkably enhanced catalytic performance is attributed to chemical modifications of the catalyst surface by the sputtered PTFE leading to a possible change in the binding strength of the intermediate species involved in the hydrogen sorption process.